Effect of exogenous thermophilic biocontrol agent inoculum on the high temperature chicken manure composting - Liu, Zuojun; Yin, Qiang; Fang, Yong; Zhang, Xueping; Xia, Wensheng; Jiao, Zhentong; Song, Tao; Wan, Heyan; Guo, Ting (Frontiers in Microbiology, 2024)
IntroductionAerobic composting is an effective method for utilizing chicken manure. However, its low carbon to nitrogen (C/N) ratio leads to slow heating and short high-temperature phases, which reduce composting efficiency and product quality.MethodsTo address this issue, splinted mushroom cultivation residues were added to adjust the C/N ratio, and exogenous thermophilic composting strains were introduced to increase composting temperature. This study analyzed the relationship between physicochemical metabolites and microbial community structure during high-temperature chicken manure composting.Results and discussionBased on metagenomic and physicochemical analyses, results showed that the exogenous microbial agents extended the thermophilic phase by three-times, reduced the heating phase duration by 75%, and increased nitrogen, phosphorus, potassium, and soluble organic carbon contents by 3.61, 21.63, 7.21, and 39.03%, respectively. Genes associated with amino acid metabolism were significantly enriched during the heating phase, while genes involved in the tricarboxylic acid cycle were more active in the thermophilic phase. During the thermophilic phase, bacterial diversity and richness decreased compared to the heating and cooling phases. Functional microbes such as Bacillus, Caldicoprobacter, and Virgibacillus showed a positive correlation with the key differential metabolites. While Actinomadura, Saccharomonospora, Paenibacillus, and Aneurinibacillus displayed an opposite correlation. Further experiments demonstrated that the increased temperature during the thermophilic phase triggered the upregulation of oleic acid metabolism and piperidine metabolism pathways in functional microorganisms, leading to the production of heat stabilizers and protective agents like oleic acid, gallic acid, and 2-piperidone. This phenomenon helped maintain microbial viability during the thermophilic phase and improved composting efficiency.